Faith-based organisations and exclusion in European cities - Beaumont, Justin; Cloke, Paul. (Bristol : The Policy Press, 2012)
This timely book explores the role played by faith-based organisations (FBOs), which are growing in importance in the provision of social services in the European context.
Ethics of workfare in the Big SocietyThe case of Pathways Ltd; Neoliberalism and faith-based engagement in progressive politics; Conclusion; 9. A shelter from the storm: faith-based organisations and providing relief for the homeless; Introduction1; The end of homelessness as we knew it; The homeless within the European framework of multiple welfare systems; Faith-based organisations and homeless service provision; Local division of labour and shifts in governance; The issue of accessibility; How faith-based organisations try to be accessible; Conclusion
Description based upon print version of record.
10. Turkish Islamic organisations: a comparative study in Germany, the Netherlands and Turkey
Keywords: Faith-based human services -- Europe; Religious institutions -- Europe; SOCIAL SCIENCE / Sociology of Religion; Electronic books